Diagnóstico do caráter coeso em solos: percepção de avaliadores e influência de atributos granulométricos - Lopes, Angélica da Silva (2023)
To establish reference values for tensile strength (TS) to assist in diagnosing the cohesive character, the following hypotheses were formulated: i) there is significant variability in the use of human perception in the qualitative assessment of cohesive character; ii) the TS for diagnosing cohesive character is influenced by soil particle size distribution; and iii) tensile strength, due to its direct and proportional correlation with cohesion, aids in quantifying the cohesive character in soils. Soil samples were collected from seven soils in six Brazilian states. The concurrent evaluation of dry-soil consistency and tensile strength using TS-Soil equipment, conducted by three evaluators, was performed on 504 aggregates/clods from each soil. TS was also measured on an equal number of aggregates/clods using an electronic dynamometer. Grain size analysis, with sand fractionation, was performed for each aggregate/clod subjected to the tensile strength test using the electronic dynamometer. Soil density was also evaluated for 504 aggregates/clods. The data were analyzed using statistical tests (Tukey and Dunnett), regression analysis, and multivariate analysis in the SAS University version software. The classification degree of sands was defined based on the standard deviation of Phi values. The threshold for TSin defining the cohesive character was ≥ 66 kPa. A high number of scores were associated with hard consistency (≥ 40 to < 66 kPa). There was a significant isolated effect of sand and clay fractions on the tensile strength of aggregates/clods. The average values of sand and clay in horizons with cohesive character showed significant effects, while the silt fraction had little influence when associated with tensile strength. For horizons without cohesive character, the models were not significant for any of the fractions. The following conclusions were drawn: i) there is a distinct perception with significant variability when human evaluators rely on subjectivity to diagnose the cohesive character in soils; ii) for different human evaluators, the threshold value of TS for the cohesive character associated with dry-soil consistency was similar; iii) the occurrence of hard consistency in horizons described with cohesive character emphasizes the need for taxonomic systems to consider at least the class with a moderate degree of cohesion in diagnosing the cohesive character; iv) the sand and clay fractions significantly influence the degree of cohesion in aggregates/clods, affecting the identification and quantification of the cohesive character in soils; v) TS is an excellent indicator to be considered in diagnosing this character in soils.